2004
DOI: 10.1051/0004-6361:20035933
|View full text |Cite
|
Sign up to set email alerts
|

An overdensity of extremely red objects around faint mid-IR galaxies

Abstract: Abstract.We have searched for Extremely Red Objects (EROs) around faint mid-IR selected galaxies in ELAIS fields. We find a significant overdensity, by factors of 2 to 5, of these EROs compared to field EROs in the same region and literature random field ERO counts. The excess is similar to that found previously in the fields of known high redshift quasars and AGN. While with the present data it cannot be definitely shown whether the overdensity is physically connected to the mid-IR source, a derived radial di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
(104 reference statements)
2
10
0
Order By: Relevance
“…Daddi et al (2000) and Roche et al (2002) have identified ERO overdensities within their surveys and argued that these may be associated with massive clusters at z k 1. Väisänen & Johansson (2004b) also report overdensities of EROs in the vicinity of faint mid-IR Infrared Space Observatory sources and argue that these may be associated with high-z clusters. Similarly enhanced ERO number densities have been reported in high-z AGN and QSO fields (e.g., McCarthy et al 1992;Hu & Ridgway 1994;Chapman et al 2000;Hall et al 2001;Best et al 2003;Wold et al 2003), although it is not yet clear whether these ERO overdensities are indeed associated with clusters linked to the central AGN.…”
Section: Discussion and Summarymentioning
confidence: 83%
See 3 more Smart Citations
“…Daddi et al (2000) and Roche et al (2002) have identified ERO overdensities within their surveys and argued that these may be associated with massive clusters at z k 1. Väisänen & Johansson (2004b) also report overdensities of EROs in the vicinity of faint mid-IR Infrared Space Observatory sources and argue that these may be associated with high-z clusters. Similarly enhanced ERO number densities have been reported in high-z AGN and QSO fields (e.g., McCarthy et al 1992;Hu & Ridgway 1994;Chapman et al 2000;Hall et al 2001;Best et al 2003;Wold et al 2003), although it is not yet clear whether these ERO overdensities are indeed associated with clusters linked to the central AGN.…”
Section: Discussion and Summarymentioning
confidence: 83%
“…Although the statistics are poor, the evidence above suggests that the different redshift distributions of the radio and ERO populations are responsible for the lack of cross-correlation signal in the bottom panel of Figure 8. The EROs peak at z k 1 (e.g., Cimatti et al 2002Cimatti et al , 2003Firth et al 2002;Väisänen & Johansson 2004a), while many of the radio sources to the flux density limit of the PDS lie at z P 1 (Georgakakis et al 1999;Afonso et al 2005;Sullivan et al 2004). This is also supported by the cross-correlation of the full radio sample with the K s -band density maps produced in x 4.1.…”
Section: Eros and The Faint Radio Populationmentioning
confidence: 80%
See 2 more Smart Citations
“…The 15 µm data, taken in the ISOCAM LW3 band and reaching approximately 0.7 mJy, are from ELAIS 15 µm Final analysis catalogue (Vaccari et al 2004), available also within the multiwavelength ELAIS Band-Merged Catalogue . The NIR observations, however, are deeper than those available in the Band-Merged Catalogue and are described in Väisänen & Johansson (2004b) in detail -essentially, we carried out a small-area survey to K < 20 mag targeting faint ISOCAM sources in approximately the range 1 to 3 mJy, without obvious counterparts in DSS images. A total of 12 ISO sources were observed in this survey, and all were found to have K-band counterparts.…”
Section: Observational Data and The Samplementioning
confidence: 99%